PENERAPAN GERAK DAN LAGU DALAM MENINGKATKAN KEMAMPUAN MOTORIK KASAR ANAK USIA 4-5 TAHUN DI SPS AZ-ZAHRA KELURAHAN SUKAMULIA KECAMATAN SAIL KOTA PEKANBARU - Yenny Zain; Zulkifli N Zulkifli N; Ria Novianti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrack : This study aims to determine how big the Implementation of Motion and songs in order to improve gross motor skills Childhood 4-5 years. This study consists of two variables: Motion and Song and gross motor. The hypothesis of this study is the adoption of Motion and Song Can Improve gross motor development Childhood 4-5 Years at SPS Az-Zahra, Village Sukamulia, District Sail, Pekanbaru